HOW SHOULD WE DISCUSS SMALL STATES? ANALYSING THE DEFINITIONS OF SMALLNESS - Lingevičius, Justinas (Politologija, 2016)
The study aims to explain the ways to discuss about small states and their foreign and security policy. Most of the academic publications dedicated to analyse the definition of small state provide different definitions based on different theories of International Relations, which also include various explanations on how size determines the behavior of a small state. These generalised explanations seem to be very limited because they are not able to give a clear understanding of why the so-called small states exercise different foreign and security policy. Therefore, another view point is chosen – to analyse the ways how states understand their smallness and what meanings define this category of size. The research is based on poststructuralism in International Relations. This theoretical perspective argues that an objective, given and materially described reality does not exist. Discursive meanings, identity and different practices of social construction are much more important objects for analysis. From this point of view, smallness is understood not as an overall and objective factor, but as an identity dimension constructed through different meanings. Two chosen cases – Lithuania and New Zealand – prove that despite the fact that both countries are understood as small, the perception of smallness and its relevance are very different. Five sizes (physical, normative, political, sovereignty and perception), used as a methodological tool, show that various meanings of being a small country are affected not only by physical size. Other factors, such as the geopolitical situation, historical memory, experience and attitude towards the international system should be taken into consideration while analysing small states and their foreign and security policy. Despite existing differences and disagreements what kind of factor (conceptual or empirical) size is, discussions about small states remain relevant because smallness can be described as one of the identity dimensions reflected by the political elite. The reflection of being a small country also shows that smallness is a political concept. Therefore, orthodox questions of what are the small states and how they behave can be changed to another one: how countries choose to be small and what they do with the different narratives of smallness. This study also suggests three principles that could be taken into consideration for further researches of small states. First, the relevance – smallness becomes relevant in concrete cases or in a relation with particular actors. Consequently, small size should not be considered as an overall fact, but only as a relative factor, relevant in a specific context. Second, identity – many endeavors to describe small state face the problem about the possibility to provide a full set of subjective characteristics explaining and covering the different aspects of a small state. One possible solution is to search for what kind of characteristics are related with smallness and which of them describe a state’s identity. Furthermore, identity presents not only the ways we describe the Self, but also how other actors react to those self-definitions do they support and admit characteristics we use to describe ourselves. Third, generalisation – there is no grounded possibility to say that one or another aspect related with Lithuania or New Zealand as a small state can be generalised or attributed to all small states. Therefore, other variables (geopolitical position, historical memory, etc.) and a broader context and relation with an international system or actors should be included into analysis.